2005
DOI: 10.1108/13552540510573383
|View full text |Cite
|
Sign up to set email alerts
|

Development of nickel‐titanium graded composition components

Abstract: The potential of various manufacturing methods was evaluated for producing nickel-titanium graded composition material. The selected test case examined attachment brackets that join nickel-based metallic thermal protection systems to titanium-based launch vehicle structure. The proposed application would replace nickel-based components with graded composition components in an effort to alleviate service induced thermal stresses. Demonstration samples were produced by laser direct metal deposition, flat wire we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(50 citation statements)
references
References 3 publications
0
49
0
1
Order By: Relevance
“…Domack and Baughman [7] also proposed the existence of a 1 mm reaction zone around the UC bond interface where the microstructure is modified, but otherwise that the microstructure of UC foils appeared unchanged. Contrary work [8] presented evidence that this is not the case in ultrasonic welding, and that the effect of the process exerts influence deeper within ultrasonically bonded aluminium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Domack and Baughman [7] also proposed the existence of a 1 mm reaction zone around the UC bond interface where the microstructure is modified, but otherwise that the microstructure of UC foils appeared unchanged. Contrary work [8] presented evidence that this is not the case in ultrasonic welding, and that the effect of the process exerts influence deeper within ultrasonically bonded aluminium.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical analysis of ultrasonically welded aluminium by Domack and Baughman [7] identified higher concentrations of carbon and oxygen within 1 mm of the weld interface. As a result of the current ambiguity over the nature of oxide dispersal, this paper intends to clarify how the surface oxides of consolidated foils are distributed within the weld interface.…”
Section: Introductionmentioning
confidence: 99%
“…the relative cost saving or cost benefits arising) has traditionally been greatest for the additive manufacture of Ni or Ti alloys. 22,23 As a result, there is a paucity of work related to the corrosion performance of the important alloy 316L, when produced by 3D printing. Of the very few works to date that report corrosion of 3D printed austenitic stainless steels, the outcomes are inconclusive.…”
mentioning
confidence: 99%
“…UC parts demonstrated good metallurgical bonding between Nickel and Titanium interfaces. The researchers concluded that all three manufacturing methods require further development before functionally graded parts can be reliably produced [29]. Liu et al also used the LENS process to fabricate functionally graded Titanium Carbide and Titanium (TiC/Ti) parts.…”
Section: Solid Freeform Fabricationmentioning
confidence: 99%